Exploring personal growth of single mother micro-entrepreneurs in Hulu Langat - Amer Hamzah, Anis Amira; AGani, Norhaninah; Fadzil, Mohd Fauzi; Yusof, Mohamed Suhaimi (Jurnal Evolusi, 2022)
There is still a great deal to learn about the entrepreneurial experience of single mothers. Based on studies on the expansion of single mother’s businesses, this paper makes its case. The data used in this study were based on recent research on single mothers in Malaysia as well as empirical facts. The entire process of becoming an entrepreneur, from seeing an opportunity to learning new skills and realizing profits, is covered under the theory of entrepreneurial value creation. Using a qualitative methodology, the data for this study was obtained. Two individuals who are members of the Women and Single Mother Society (WITUS) and are also entrepreneurs were interviewed in-depth. The results showed that the primary obstacles were the lack of entrepreneurial abilities and business resources, the problem of social stigma, and the difficulty of striking a balance between their personal and professional obligations. Entrepreneurs who are single mothers primarily rely on their personal resources and unofficial support network to sustain their company. The informal support structure, while helpful, is unable to reinforce their personal financial situation and ensure the continued existence of their enterprises. These entrepreneurs are single mothers, yet it doesn’t appear like personal problems are holding them back. Both direct and indirect consequences of knowledge barriers are felt by growing businesses. As seen in this context, the obstacles are caused by a low degree of expertise in management.